Hemoglobin levels and blood pressure are associated in rural black africans. Issue 1 (19th June 2015) - Rasmussen, Jon B.; Mwaniki, David L.; Kaduka, Lydia U.; Boit, Mike K.; Borch‐Johnsen, Knut; Friis, Henrik; Christensen, Dirk L.
Abstract : Objectives: The association between blood levels of hemoglobin (B‐hgb) and blood pressure (BP) has been widely investigated in Caucasians and Asians but there is a paucity of data in rural black Africans. The objective was to investigate the association between B‐hgb and BP in a rural black African population. Methods: A cross‐sectional study was conducted in three districts in Kenya (Bondo, Kitui, and Transmara) with the inclusion of participants aged ≥17 years. Background information, anthropometry, BP, B‐hgb, hepatic insulin resistance (HOMA2‐IR), standard lipid profile, and oral glucose tolerance test were obtained in each participant. Results: Background characteristics among 1, 167 participants showed that anemic and non‐anemic participants differed significantly from each other as there were more women, lower body mass index and waist circumference (WC), lower degree of hepatic insulin resistance and plasma cholesterols among the anemic participants. Furthermore, anemic participants had significantly lower systolic and diastolic BP ( P  < 0.01) but not a significantly different prevalence of hypertension ( P  = 0.08). Multivariate linear regression models adjusted for—age, sex, plasma total‐cholesterol, WC, Log2(HOMA2‐IR), ethnicity, and smoking status—revealed that B‐hgb (per mmol/l increment) was significantly associated with systolic BP (estimate: 1.18 (0.37–1.98)) and diastolic BP (estimate: 1.06 (0.54–1.57)) ( P  < 0.01). Conclusions: B‐hgb is associated with BP in rural black Africans. Am. J. Hum. Biol. 28:145–148, 2016. © 2015 Wiley Periodicals, Inc.